Self-directed learning pada pendidikan orang dewasa di Indonesia: sebuah tinjauan sistematis untuk mewujudkan pendidikan berkualitas dan inklusif - Muhamad Yusuf Wijayakusuma; Dadang Yunus Lutfiansyach; Joni Rahmat Pramudia; Deti Nudiati (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2025)
As new learning methods continue to emerge, Self-Directed Learning (SDL) remains a crucial element in the field of education, specifically for promoting inclusive quality education. This research is a Systematic Literature Review using the PRISMA framework to explore research trends, factors, and impacts of self-directed learning within Indonesian adult education, focusing on 25 Scopus-indexed publications from 2019 to 2024. The findings indicate a notable rise in related publications, particularly post-2022, with quantitative research methods being the most applied and undergraduate students serving as the primary subjects, which highlights a gap in representing broader adult learner populations. Thematic analysis reveals that SDL is effectively cultivated through structured antecedents, specifically gamified MOOCs, Learning Management Systems, and flipped classroom pedagogies, which causally link to enhanced digital literacy, creativity, and learner autonomy. Crucially, the study distinguishes that while purposeful educational technology fosters independence, uncontrolled social media usage acts as a potential hindrance to self-regulation. Based on these insights, the researchers recommend prioritizing guided technology integration and suggest that future studies diversify methodologies and broaden participant scopes beyond undergraduate students to better address the inclusive nature of adult education. Aligning with SDG 4 and SDG 10, this study positions SDL as a catalyst for inclusive quality education and reduced inequalities, empowering diverse learners, particularly marginalized groups, to achieve autonomy and lifelong growth.